Muda forzada o "reciclaje" de gallinas ponedoras en piso : resultados de estudios de campo - Zumbado Alpízar, Mario Ernesto 1955-
Force molting of laying hens housed in littered floors. Results of field studies. Very little information is available on force molting of hen flocks housed in floors and litter facilities instead of cages. A field study was conducted with nine Isa-Brown flocks averaging 8,100 hens per flock, together with information from one Isa-Babcock B-300 white hen's flock. A conventional fasting, no artificial light molting program, was implemented in all flocks The fasting period averaged 13.2 days, with a minimum of 9 and a maximum of 15 days. This was the necessary period of time for the flocks to stop laying eggs and lose enough body weight. Flocks stopped production at 12.2 days without feed (11 min, 13 max); however, two flocks never stopped laying hens, and their lowest laying rate was 0.9 and 0.4% hen-day. The white flock halted production after 6 days of fasting. Average weight loss for the brown hens was 20% and 24.2% at 10 and 14 days of fasting, respectively (18.3 and 27.3% for the white flock). The daily weight loss ranged from 1.7 to 2.2%. The day previous to start the molting program, the average laying rate was 70.3% hen-day (60.0-78.8%) at 70.6 (65.0-76.0) weeks of age From the first egg after molting to 50% production, the flock averaged 17.6 (13.0-22.0) days, and peak egg production was 77.2% (67.2-84.2%) hen-day. It took the brown hen flocks an average of 34 days to reach 50% egg production from the first day of fasting. The white flock lasted 41 days to reach 50% production. The brown flocks reached 6.9% (1.9-10.7%) egg production above the level they had the day prior to the start of the molting program and stayed 12 (6-21) weeks above that laying rate value. They remained for 2.2 (0-8) weeks above 80% hen-day egg production. Hen mortality averaged 0.35%/week (0.11-0.85) during the 40 days after fasting started. These data with hens on littered floors are quite different compared to the information available on force molting...